Analysis of Application of Accounting Infromation Systems Sales of Rooms and Acceptance of Cash on Griya Penanggungan Kediri City - Dyah Ayu Paramitha (CAHAYA AKTIVA, 2021)
This study aims to analyze and determine the application of accounting information systems for sales of rooms and cash receipts at Griya Penanggungan Kota Kediri. The research method used is descriptive qualitative research because this study aims to compare with existing theories. The types of data used are primary data and secondary data. Primary data in question is data from interviews, while secondary data is information about company history and accounting information systems. The results of this study prove that the accounting information system for room sales and cash receipts at Griya Penanggungan Kota Kediri is good enough; sales made with cash sales systems and credit sales have been running according to existing procedures. However, there are still weaknesses in planning and control, namely the absence of regular budgeting. Keywords: accounting information system, sales accounting, cash receipts